Media related articles in the Algerian Penal code a comparison between penal code2001 and2011 - madah, khaldia (Journal of Social Sciences and Humanities, 2021)
Freedom of the media is among the most important freedoms in the modern era. If this freedom is restricted, the press will lose an important function which is enlightening society with facts - which implies under the public’s right to information, and transcending this freedom to the limits stipulated by law to protect individuals, society and the state. Organizing this freedom within a framework of a balance between it and other rights, by setting boundaries that must not be crossed, and in return not compromissing its essence. Legislation is the legal framework regulating public freedoms, including freedom of the media, so defining the field of exercising public freedoms is within the jurisdiction of the legislator that defines its legal system, and it is his duty to clearly regulate these freedoms as a guarantee for them, and it defines them specifically required by the prevailing social, economic and political situation in society, and when the legislator intervenes In defining public freedoms, he does not restrict them but rather provides legal grounds that help him defend the individual's rights and freedoms, and also prejudices these freedoms as punishment, and the Penal Code is the one that decides this punishment. Opinions differed greatly regarding the estimation of penalties in this law, especially those related to the media, considering that the latter is nothing more than an idea, and this idea never rises to the penalties prescribed for other crimes, and if we look at all the legislation in the majority of countries, we find it converging in the text of the penalties The decisioner, especially with regard to freedom of the media and stipulated by international agreements to regulate this field, and Algeria, like other countries ratifying these agreements, is also trying to find ways to protect this freedom by stipulating what ensures a balance between it and other freedoms.